“Don’t Just Collect Words”: Strategies for Advanced Indigenous Language Learning - Benson, Nicki (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2024)
Advanced adult Indigenous language speakers are essential in Indigenous language revitalization (ILR). As first language speakers age and pass away, communities increasingly depend on adults with high proficiency to carry the language forward (Fishman, 1991; Hinton, 2011; W.H. Wilson, 2018). Yet, few studies in ILR focus on adult learners, and fewer still on adults working on advanced proficiency. Similarly, in the field of applied linguistics (AL), minimal attention has been given to strategies for advanced language learning, and less still to Indigenous language learning (Daniels & Sterzuk, 2022; McIvor, 2020). This paper presents the results of a study aimed at understanding how adult Indigenous language learners have achieved advanced proficiency, including cases where there are few or no first language speakers to rely on for mentorship. It presents specific strategies and techniques that participants implemented to successfully progress to advanced proficiency. Insights from this context are shared to further understandings of, and possibilities for, greater connections between AL and ILR.